(Un)visible and (un)speakable from/of student life at the univers/cities - Machado, Jardel Pelissari; Zanella, Andrea Vieira (Universidade Estadual de Campinas, 2021)
This text aims to analyze verbal and image statements, student responses to social voices that produce the space-times, conditions and possibilities of / in university academic life and that express some form of suffering. These statements, dialogues (transcripts) and photographs, were produced in the context of Photography Workshops, which comprised a doctoral research-intervention in psychology, by undergraduate students (a total of 16 participants) of a Brazilian federal university. We discussed these statements as a product/reflection of exclusion in the academic university context, which is, in most cases, silenced and invisible in the midst of logics of productivity, costs, rankings, among others. We conclude on the need to build spaces were the voices of the students can circulate, be heard/read, so that they can effectively assist in the construction of universities and the conditions and possibilities of academic life.